Investigating barriers to effective communication in the lecturing environment at CUT - Vogt, Emmanuel Rasdien (Central University of Technology, 2021)
Effective communication in the lecturing environment plays an important role in assisting lecturers and students in achieving educational outcomes. However, the problematic nature of communication barriers could impede communication and lead to ineffective teaching and learning. Consequently, ineffective communication has a negative impact on student achievement. In contrast, effective communication could minimise miscommunication and lead to improved student performance. As such, this study investigated the barriers to effective communication in the lecturing environment. A quantitative approach, using an interpretive and explorative design, was used to investigate the extent to which communication barriers influence learners’ performance in the classroom. Data was collected using questionnaires that were designed for lecturers and students, respectively. The study revealed that communication barriers do in fact influence students’ performance adversely and that they are still prevalent in the lecturing environment. The researchers recommend that barriers should be reduced to improve learner performance.
Thesis (Master: Communication: Language practice)--Central University of Technology
Keywords: Communication skills; Communication barriers; Teaching and learning